Development of an instructor laboratory teaching effectiveness scale and an achievement test in marine engineering - Dalaguete, Felicito P. (Animo Repository, 1992)
This is a study on the development and validation of an instrument for assessing laboratory teaching effectiveness and an achievement test for marine engineering graduates, using the descriptive-developmental type of research. The samples of this study were composed of six maritime schools. Seven laboratory classes from these schools were purposively selected. A total of 150 students from seven marine engineering laboratory classes were randomly selected to validate the Laboratory Teaching Effectiveness Scale (LABTEST). Likewise, a total of another 150 graduating marine engineering students as of October 1991 were also randomly chosen to validate the Maritime Standardized Achievement Test (MSAT). Factor Analysis and a one-way repeated measures test was applied in the validation process of the LABTEST. On the other hand, the MSAT was validated with the use of item analysis, concurrent validity and internal consistency. The norms of the test were also established. All data gathered from the sample schools using the LABTEST and MSAT instruments were computerized. The LABTEST had 4 dimensions, namely: Laboratory Class Management with 10 identified indicators Knowledge and Mastery of Laboratory Activities with also 10 indicators Organization and Planning of Laboratory Activities with 5 indicators and Laboratory Instructor's Motivational Skills with 5 indicators. The 30 indicators of the LABTEST had varying degrees of discriminant values ranging from .436 to .753 which were described from satisfactory to substantial or high (Lyman, 1971) and had greater correlation with the criterion (Guilford, 1973). Likewise, the 4 dimensions had sufficient area reliability coefficients ranging from .75 to .91 with substantial overall reliability coefficient of .84 for purposes of faculty evaluation (Kohler, 1976).On the other hand, MSAT had a total of 150 test items distributed under 10 sub-areas: Engine Room Mathematics, Ship Nomenclature and Basic Naval Architecture, Machine Shop Practice, Marine Electricity and Electrical Machinery, Marine Electronics and Automation, Marine Auxiliary System and Machinery, Steam Engineering, Internal Combustion Engine, Safety of Life at Sea, and Maritime Law and Engine Watchkeeping. Individual items had discrimination indices ranging from .114 to .600 considered as satisfactory (Garrett, 1965) and could positively discriminate among examinees (Guilford, 1973). The difficulty indices ranged from easy (.820) to difficult (.133). The examinee's test scores on lecture subjects: SNBNA (.270), ERM (.291) and MLEW (.196) were significantly related with their grade point average (GPA) at .01 and .05 levels of significance. Similarly, students' GPAs in subjects with both lecture and laboratory components (ICE, r=.184) supported with adequate facilities were also significantly related at .05 GPA. The conclusions derived from the findings were: 1) LABTEST has satisfactory validity and sufficient reliability for purposes of evaluating marine engineering laboratory instruction. 2) MSAT possesses substantial validity and reliability for purposes of achievement testing graduating marine engineering students.